The temperament features associated with autism spectrum disorder in childhood: A systematic review. (September 2020) - Mallise, Carly A.; Lane, Alison E.; Woolard, Alix J.; Whalen, Olivia M.; Murphy, Vanessa E.; Karayanidis, Frini; Campbell, Linda E.
Highlights: In early infancy, infants later diagnosed with ASD had 'easy' temperament features. In mid to late infancy, temperament of infants later diagnosed with ASD was reported to be more challenging. Children with ASD displayed more challenging temperament features than typically developing peers. Further research is needed into the variability of temperament in children with ASD. Abstract: Background: Temperament is an important construct that shapes child development. Temperament is suggested to present differently in different groups, such as children with neurodevelopmental disorders. However, it is not known whether there are specific temperament features associated with Autism Spectrum Disorder (ASD). Aim: This systematic review aimed to synthesise extant literature to determine whether there are temperament features associated with ASD in infancy, toddlerhood and childhood. Methods and Procedures: Following the PRISMA guidelines for systematic reviews, we searched PsycINFO, CINAHL, Academic Search Ultimate and ProQuest for all available articles from database conception until January 2020. The Joanna Briggs Institute Critical Appraisal checklists were used to assess the methodological quality of included articles. Outcomes and Results: Twenty-six articles met the selection criteria: (1) reported on the temperament of children (0–12 years of age) diagnosed with ASD, (2) peer-reviewed; and (3) published in English. Articles varied in overall methodological quality. Infants later diagnosed with ASD were found to more frequently be described as having 'easy' temperament features in early infancy, compared to typically developing infants and infants with developmental concerns but not ASD. Once diagnosed, children with ASD were reported to, as a group, display more negative affect, less extraversion and less effortful control than typically developing children. Conclusions and Implications: The literature suggests that more challenging temperament features are associated with ASD in childhood, but less is known about within group variability. Overall, this review highlights the need for further investigation into the variability of temperament in children with ASD.